Antioxidative potential and ameliorative effects of green lentil (Lens culinaris M.) sprouts against CCl4-induced oxidative stress in rats - Barakat, Hassan; Alshimali, Saleh I.; Almutairi, Abdulkarim S.; Alkhurayji, Raghad I.; Almutiri, Sarah M.; Aljutaily, Thamer; Algheshairy, Reham M.; Alhomaid, Raghad M.; Aljalis, Rashed A.; Alkhidhr, Mohammed F.; Abdellatif, Ahmed A. H. (Frontiers in Nutrition, 2022)
The present study is aimed to investigate the antioxidative potential and ameliorative effects of Lens culinaris Medikus sprouts hydroalcoholic extract (LSHE) on CCl4-induced oxidative stress in rats. The research has been carried out in two successive stages. Firstly, the highest phenolic content and antioxidant activity of L. culinaris sprouts were assessed at 20±1°C and 90-93% RH during sprouting. Total phenolic content (TPC), total carotenoids (TC), total flavonoids (TF), total flavonols (TFL), DPPH-RSA, and vitamin C contents of L. culinaris seeds and 6-days sprouts were determined. Subsequently, phenolics by HPLC analysis of L. culinaris seeds, 3rd, and 6th-day sprouts were identified and quantified. Results indicated that 6th-day sprouts contained considerable phenolics with superior antioxidant capacity, thus selected to be examined for biological activity in a rat’s module consisting of 5 groups. G1, normal rats orally received distilled water. G2 received 1.0 mL kg-1 of CCl4 and olive oil (1:1) intraperitoneally (i.p.) twice a week. G3 received CCl4 (i.p.) and 50 mg GAE kg-1 of LSHE daily/orally. G4 received CCl4 (i.p.) 100 mg kg-1 of LSHE orally/daily. G5 (reference group) treated by intramuscular injection (i.m.) of vit. E+Selenium (Vit. E+Se, 50 mg kg-1 twice a week). The weight gain, relative weight of organs, hypoglycemic and hypolipidemic efficiencies, liver’s and kidneys’ functions, and antioxidant biomarkers were examined. LSHE enhanced the weight gain recovery % and significantly reduced fasting blood glucose. The hypolipidemic effect of LSHE was dramatically reduced triglycerides (TG), total cholesterol (CHO), high- and low-density lipoproteins (HDL-c and LDL-c), and very-low-density lipoproteins (VLDL-c). Administration of 50 and 100 LSHE mg kg−1 ameliorated liver and kidney function in dose-dependent manure. Intriguingly, LSHE considerably reduced malondialdehyde (MDA) while significantly raising reduced glutathione (GSH), superoxide dismutase (SOD), and catalase (CAT) in a dose-dependent manner. In conclusion, biochemical examinations confirmed the therapeutic efficacy of LSHE as a functional product. It encouraged us to recommend L. culinaris sprout production for attenuating hepatotoxicity and nephrotoxicity, as well as being beneficial and profitable for controlling oxidative stress complications.